(The Juristic Reference of the Foundations of Constitutions (An Empirical Study on Sudan's Interim Constitution of 2005 - Timsah, Mohamed Hassan Gamaa (Journal of Economic, Administrative and Legal Sciences, 2018)
The written constitution is the basic document and the nominal charter between the ruler and the governed. The source of the will is the will of the people and it is considered the principles and aspirations of the people on how to organize the public authorities and determine their powers in the state and its structures. The nature of this study requires that we take the descriptive, analytical and applied approach to research from the jurisprudential reference to the methods of establishing constitution and the manner of their development. This is done in four sections dealing with the concept of the constitution and its types, and the methods of establishing democratic and non-democratic constitutions in traditional and modern constitutional jurisprudence. The constitution and its constitution dealt with the most important features of the Constitution of the Sudan Transitional Law for the year 2005, which is effective in terms of its themes and the manner of its development. The conclusion of the study is the most important conclusions and recommendations: that the development of the constitution in the form of grant or contract non-democratic - robbing the will of the people in the constitution and to give the legal value of the Constitution. The most important recommendations of the study were the need to establish constitutions in a democratic manner. The constitution's entry into force in this manner means the sovereignty of the people's will to make constitutions and the principle of legality, as well as the expression of the values ​​and principles of the people.
Keywords: reference; jurisprudence; methods; emergence; constitutions